PENDAMPINGAN PENYUSUNAN STANDAR PELAYANAN PUBLIK MELALUI FORUM GROUP DISCUSSION DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TULUNGAGUNG - pengabdian; Anang Sugeng Cahyono; Retno Sari Dewi; Asmah Asmah; Dwiatmanto; Ina Heliany (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Regency as part of the local government has an obligation to provide quality public services. The benchmark is carried out through public service standards that are service guidelines. According to the regulations, the disdukcapil is required to involve external parties such as the community, academics and others to jointly develop service standards. The purpose of community service activities and the role of FISIP Universitas Tulungagung is to provide assistance in the preparation of service standards for the Tulungagung Regency Disdukcapil. The method used was through Focus Group Discussion (FGD). As a result of this activity, there are policies in the form of decrees on the determination of service standards and service standard documents of the Tulungagung Regency Disdukcapil. The consistency and continuity of this activity needs to be carried out in accordance with changes in regulations and the growing demands of service users.